Livelihoods and welfare: Findings from the seventh round of the Myanmar Household Welfare Survey (January–June 2024) - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
The seventh round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was implemented between April–June 2024 with a recall period covering January to June of the same year. It follows six rounds of surveys that were carried out since the beginning of December 2021. This report documents livelihood and welfare dynamics over this survey period. Overall, household welfare has deteriorated in Myanmar considerably over the past two years. In terms of income sources, household farming, farm wages, and non-farm businesses are the most important livelihoods in rural areas while non-farm businesses and non-farm salary employment are most important in urban areas. However, in terms of primary livelihoods, we witness a structural shift in livelihood profiles of rural households with fewer households identifying non-farm business income are their primary livelihood (4.1 percentage points decrease) while more households rely on farm wages (2.9 percentage points increase). There are also fewer reported sources of income with households on average reporting 1.6 income sources, compared to almost 2 years ago. The primary source of income is shifting to low-paying livelihoods like wage work, with remittances and assistance serve as supplementary income sources. A combination of increasing prices and growing reliance on low paying livelihoods over the past years led to a significant decline in household purchasing power. Median real household income per adult equivalent per day declined by 8.4 percent over the past year between the first half of 2023 and 2024 and by 18.2 percent over the two-year period between the first half of 2022 and 2024. Over the same period, the headcount rate of poverty increased to 63.6 percent in the first half of 2024 from 60.9 percent a year back in 2023 and 56.2 percent two years back in 2022. Wage earning households continue to be extremely vulnerable with the lowest median real daily income per adult equivalent as well as the livelihood category with the highest level of poverty. With respect to states/regions, poverty is the highest in states engulfed by high levels of conflict, for example, Rakhine, Chin and Kayah. A notable trend in recent years is the faster increase in urban poverty. Urban poverty increased by 9.2 percentage points over the past year from the first half of 2023 to the first half of 2024, while it increased by 14.7 percentage points over the past two years from the first half of 2022 to first half of 2024. On the other hand, rural poverty only increased by 0.2 percentage points in the past year and 4.6 percentage points in the past two years. There are only a few strategies helping households stay out of poverty, including earning income from farming (which has partially benefited from higher output prices), migrating with the whole household, and receiving assistance or remittances. The presence of remittance income significantly reduces a household’s probability of being poor by a notable 21 percentage points. There are many inter-linked factors that have led to the deterioration in welfare in Myanmar in recent years, including escalating conflict, macroeconomic mismanagement and inflation in particular, the breakdown of social protection, and the absence or deterioration of many other critical services normally provided by the state, including healthcare and nutrition, education, agricultural extension, financial programs for the poor, infrastructure development and social protection.